Multi-Omics Analysis of Gene and Protein Candidates Possibly Related to Tetrodotoxin Accumulation in the Skin of Takifugu flavidus - Huimin Feng (MDPI AG, 2021)
Pufferfish is increasingly regarded by many as a delicacy. However, the tetrodotoxin (TTX) that accumulates in its body can be lethal upon consumption by humans. TTX is known to mainly accumulate in pufferfish skin, but the accumulation mechanisms are poorly understood. In this study, we aimed to explore the possible mechanism of TTX accumulation in the skin of the pufferfish Takifugu flavidus following treatment with TTX. Through liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, we detected 37.3% of toxin accumulated in the skin at the end of the rearing period (168 h). Transcriptome and proteome analyses revealed the mechanism and pathways of TTX accumulation in the skin of T. flavidus in detail. Gene ontology and the Kyoto Encyclopedia of Genes and Genomes analyses strongly suggest that cardiac muscle contraction and adrenergic signaling in cardiomyocyte pathways play an important role in TTX accumulation. Moreover, some upregulated and downregulated genes, which were determined via RNA-Seq, were verified with qPCR analysis. This study is the first to use multi-omics profiling data to identify novel regulatory network mechanisms of TTX accumulation in the skin of pufferfish.